Prediagnostic plasma folate and the risk of death in patients with colorectal cancer - Wolpin, Brian M. (2008)
PURPOSE: Although previous studies have demonstrated an inverse relationship between folate intake and colorectal cancer risk, a recent trial suggests that supplemental folic acid may accelerate tumorigenesis among patients with a history of colorectal adenoma. Therefore, high priority has been given to research investigating the influence of folate on cancer progression in patients with colorectal cancer. METHODS: To investigate whether prediagnostic levels of plasma folate are associated with colorectal cancer-specific and overall mortality, we performed a prospective, nested observational study within two large U.S. cohorts, the Nurses’ Health Study and Health Professionals Follow-up Study. We measured folate levels among 301 participants who developed colorectal cancer 2 or more years after their plasma was collected and compared participants using Cox proportional hazards models by quintile of plasma folate. RESULTS: Higher levels of plasma folate were not associated with an increased risk of colorectal cancer-specific or overall mortality. Compared with participants in the lowest quintile of plasma folate, those in the highest quintile experienced a multivariable-adjusted hazard ratio for colorectal-cancer-specific mortality of 0.42 (95% CI, 0.20–0.88) and overall mortality of 0.46 (95% CI, 0.24–0.88). When the analysis was limited to participants whose plasma was collected within 5 years of cancer diagnosis, no detrimental effect of high plasma folate was noted. In subgroup analyses, no subgroup demonstrated worse survival among participants with higher plasma folate levels. CONCLUSION: In two large prospective cohorts, higher prediagnostic levels of plasma folate were not associated with an increased risk of colorectal cancer-specific or overall mortality.